FOREIGN SHARE OWNERSHIP LIMITS IN THE BUSINESS FIELD OF MINERAL AND COAL MINING ON PEOPLE’S WELFARE - Ida Sumarsih (Problematika Hukum, 2019)
Natural Resources as an unrenewable resources are a gift from God Almighty and owned by the Indonesian people, according to Article 33 paragraph (3) of the 1945 Constitution, and their management must be used to realize people’s welfare. In practice, the management of mineral and coal mining is carried out by involving foreign investors who require security guarantee for their business and investment. This research aims to answer the problem regarding setting limits on foreign share of ownership in the mineral and coal mining business sector in Indonesia and its implementation. This problem is then used as a basis for consideration to realize policies that have legal certainty to support efforts to realize people’s welfare. This study uses two theories, namely the purpose of law (Gustav Radburch) and the theory of the legal system (Lawrence Friedman). The research method used is normative juridical with empirical juridical support.The findings of the research show that in enforcing limits on foreign share ownership there is still law smuggling, for example through borrowing names or nominees to secure the interests of foreign investors even though normatively they do not fulfill the legal terms of agreement as stipulated in article 1320 of the Civil Code. For investors the nominee agreement is a legal solution to ensure the security of investment in the mining sector in Indonesia. Therefore, the state needs to carry out supervision and law enforcement so that limitation on foreign share ownership can be implemented in accordance with the applicable laws and regulations. So that the purpose of exploiting mineral and coal mining for the welfare of the people in the mining sector can be realized and in